2011
DOI: 10.1007/s10593-011-0729-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative amination and hydroxylation of 1,3,7-triazapyrenes in aqueous medium

Abstract: We have already reported the unusual capacity of 1,3,7-triazapyrenes 1a and 1b [1] and 7-alkyl-1,3,7-triazapyrenium salts [2][3][4][5] to react readily in aqueous solution with O-nucleophilic reagents to give mono-and disubstitution products. This is the result clearly not only of the -electron deficiency of these compounds but also the specific peri-fusion structure of this heterocyclic system.The oxidative amination of the most electrophilic heterocycles such as naphthyridines [6] or 1,2,4-triazine [7] is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…15 In our previous reports, we have shown that 1,3,7-triazapyrene (1a) displays special properties due to the unique fusion of the carbocyclic and heterocyclic rings. These properties include an unusual ease of oxidative nucleophilic substitution of hydrogen, such as hydroxylation, 21 and even amidation. 28 Another unusual feature of 1,3,7-triazapyrenes is that the greater part of these transformations can be carried out in aqueous media.…”
Section: Methodsmentioning
confidence: 99%
“…15 In our previous reports, we have shown that 1,3,7-triazapyrene (1a) displays special properties due to the unique fusion of the carbocyclic and heterocyclic rings. These properties include an unusual ease of oxidative nucleophilic substitution of hydrogen, such as hydroxylation, 21 and even amidation. 28 Another unusual feature of 1,3,7-triazapyrenes is that the greater part of these transformations can be carried out in aqueous media.…”
Section: Methodsmentioning
confidence: 99%